The effects of different antioxidant agents on the microtensile bond strength of composite resin to bleached enamel = Efecto de diferentes agentes antioxidantes en la resistencia a la microtracción de la resina compuesta al esmalte blanqueado - Ozakar Ilday, Nurcan
The objective of this in vitro study is to examine the effect of antioxidants on the bonding strength of composite resin to bleached enamel. One hundred twenty non decay teeth were used in this study. Specimens were cut from the enamel cement junction. Then the specimens were randomly assigned into two groups-office bleaching and home bleaching. Bleaching antioxidants were applied to the first 12 subgroups. The specimens in the remaining 12 groups were kept in artificial saliva for 14 days and antioxidants were applied. Composite resin restoration was applied to all specimens. A cutting device was employed to obtain six specimens (0.9mm) from each tooth, and the microtensile bond strength (μTBS) test was performed. Data were analyzed using one-way ANOVA, the paired t-test, and Duncan's post hoc test (p=0.05). In office bleaching specimens, immediate antioxidant application increased the μTBS values (p<0.05). Comparisons of the antioxidants individually revealed that bonding values increased after two weeks in specimens subjected to antioxidant application (p<0.05). In office bleaching specimens, immediate antioxidant application increased the μTBS values (p>0.05). Mean μTBS values in the groups to which antioxidants were applied two weeks after home bleaching were higher than those in the groups in which antioxidants were applied immediately. The use of antioxidants after bleaching may increase the MTBS value. The clinician should take this into account especially in immediate restoration applications after bleaching.